2023
DOI: 10.13073/fpj-d-22-00049
|View full text |Cite
|
Sign up to set email alerts
|

Financial Analysis of Innovative Wood Products and Carbon Finance to Support Forest Restoration in California

Abstract: Traditional funding strategies of grants, congressional appropriations, and income from timber sales are insufficient to complete the level of forest restoration necessary throughout California. Stimulating investment into markets for low-value biomass—such as tops and branches of trees, small trees, and dead trees—will add value to forest raw materials and provide additional revenue streams to pay for forest restoration. We evaluate the investment potential of products made from low-value biomass using a disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Co-benefits are not limited to land-based CDR. In fact, scientists are studying how forest biomass with carbon capture and storage can reduce the risk of wildfires when paired with forest thinning projects (Sanchez et al 2021;Elias et al 2023). Social cobenefits for industrial CDR with carbon capture and storage could include jobs or economic revenue in areas and fields affected by the energy transition (Romig 2021).…”
Section: Robust Measurement Reporting and Verification Systems Are Ne...mentioning
confidence: 99%
“…Co-benefits are not limited to land-based CDR. In fact, scientists are studying how forest biomass with carbon capture and storage can reduce the risk of wildfires when paired with forest thinning projects (Sanchez et al 2021;Elias et al 2023). Social cobenefits for industrial CDR with carbon capture and storage could include jobs or economic revenue in areas and fields affected by the energy transition (Romig 2021).…”
Section: Robust Measurement Reporting and Verification Systems Are Ne...mentioning
confidence: 99%
“…Technological and business research aims to assess the cost feasibility of processes for using wood biomass to produce a specific type of energy product [38][39][40] or wood product [52][53][54][55][56][57]. Business evaluation involves comparing the use of different raw materials [58][59][60][61], pre-processing technologies [62,63], product manufacturing [29,[64][65][66], plant locations [67][68][69], or alternative products [70][71][72][73] in supply chain configuration. The most frequent business indicators in this group of studies were the obtained manufacturing cost ratios and the internal rate of return of the adopted technology.…”
Section: Business Evaluationsmentioning
confidence: 99%
“…Only recently has forest restoration been studied from a socioeconomic perspective around the world [8,52,[86][87][88]. In California, Elias et al [89] showed that the exploitation of several, highly profitable products from forest restoration is not only possible but can provide financial support for the restoration efforts. In addition, Montagni and Piotto [90] found that revenues from timber harvesting can exceed the costs of establishing and managing mixed plantations of native species.…”
Section: Socioeconomic Outcomes Reported In the Studiesmentioning
confidence: 99%